2023
DOI: 10.1001/jamanetworkopen.2023.1572
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Buprenorphine Initiation in the Emergency Department Among Patients Using Fentanyl and Other Opioids

Abstract: This cohort study examines buprenorphine treatment initiation, response, and follow-up among patients presenting to California emergency departments (EDs) who reported fentanyl or other opioid use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…8 High-dose buprenorphine is another initiation strategy where opioid discontinuation is followed by rapid HDB (≥8 mg starting dose). 11,12 This strategy is based on the premise that increasing initial doses of buprenorphine beyond 8 mg sublingual (SL) will result in increasing agonist MOR activation and strengthening opioid blockade-both conferring significant advantages. Typically, HDB expects a period of opioid abstinence, which is highly variable.…”
Section: Consideration Statements Kq1: What Specific Clinical Situati...mentioning
confidence: 99%
See 2 more Smart Citations
“…8 High-dose buprenorphine is another initiation strategy where opioid discontinuation is followed by rapid HDB (≥8 mg starting dose). 11,12 This strategy is based on the premise that increasing initial doses of buprenorphine beyond 8 mg sublingual (SL) will result in increasing agonist MOR activation and strengthening opioid blockade-both conferring significant advantages. Typically, HDB expects a period of opioid abstinence, which is highly variable.…”
Section: Consideration Statements Kq1: What Specific Clinical Situati...mentioning
confidence: 99%
“…4 In addition, 2 retrospective cohort studies of HDB across 16 EDs reported no increased adverse events compared with standard initiation; however, 1 study occurred before widespread HPSO, and the other reported a low incidence of HPSO use. 11,12…”
Section: Consideration Statements Kq1: What Specific Clinical Situati...mentioning
confidence: 99%
See 1 more Smart Citation
“…A qualitative study of hospitalist perspectives on buprenorphine identified a lack of training, inpatient management resources, and community referral networks as barriers to prescribing 7 . Hospitalists may also be concerned about precipitating opioid withdrawal in the setting of lipophilic opioids like fentanyl 8 . Finally, stigma is a barrier to prescribing buprenorphine among clinicians 9 .…”
Section: Policy In Clinical Practicementioning
confidence: 99%
“…7 Hospitalists may also be concerned about precipitating opioid withdrawal in the setting of lipophilic opioids like fentanyl. 8 Finally, stigma is a barrier to prescribing buprenorphine among clinicians. 9 Efforts to address these barriers include educational interventions, prescribing champions, toolkits with training resources, institutional protocols and order sets, and addiction consult teams.…”
Section: Terminology and Acronyms Background And Historymentioning
confidence: 99%